Impressions of action and critical action learning: exploring the leadership development of senior doctors in an English healthcare organization. (26th January 2018) - McCray, Janet; Warwick, Rob; Palmer, Adam
Abstract : This paper aims to explore the influence of one cycle of a learning set experience in a postgraduate medical leadership development programme. It does so from two perspectives: first, from the self‐reports of nine senior doctors working in leadership roles in England in the National Health Service; and second from a researcher perspective as we present our research process, findings and perceptions on the use of action learning (AL) and critical action learning (CAL) for leadership development in the complex and unpredictable context of that service. The paper affirms other study findings that CAL in the development of participants' collective reflexivity has the potential to deal with emotions and power relations in organizational life. An original contribution lies in advancing the idea that CAL can help build resilience in doctor leaders and groups in uncertain conditions such that they are able to challenge current care delivery and effect change in organizational performance.